Pathogenic role of anti-β2-glycoprotein I antibodies in antiphospholipid associated fetal loss: characterisation of β2-glycoprotein I binding to trophoblast cells and functional effects of anti-β2-glycoprotein I antibodies in vitro. Issue 3 (15th July 2004) - Di Simone, N; Raschi, E; Testoni, C; Castellani, R; D'Asta, M; Shi, T; Krilis, S A; Caruso, A; Meroni, P L
Abstract : Background: Antiphospholipid antibodies reacting with β2-glycoprotein I (β2GPI) have been associated with recurrent fetal loss and pregnancy complications. Objective: To investigate whether specific mutations in the phospholipid binding site of β2GPI might affect its binding to trophoblast and in turn the anti-β2GPI antibody induced functional effects. Methods: β2GPI adhesion to trophoblast was evaluated as human monoclonal IgM or polyclonal IgG anti-β2GPI antibody binding to trophoblast monolayers cultured (1) in complete medium; (2) in serum-free medium; (3) after serum starvation in the presence of purified human β2GPI; or (4) in the presence of β2GPI with single or multiple mutations in the amino acid loop Cys 281 -Lys-Asn-Lys-Glu-Lys-Lys-Cys 288 . The effect of anti-β2GPI binding to trophoblast was evaluated as chorionic gonadotropin (hCG) mRNA expression, and protein release by RT-PCR and radioimmunoassay, respectively. Results: β2GPI adhesion to trophoblast and its consequent recognition by the specific antibodies were inversely proportional to the mutation number in the phospholipid binding site. Anti-β2GPI antibodies reduced gonadotropin release, hormone dependent hCG mRNA expression, and protein synthesis in the presence of β2GPI, while the addition of the mutants or the absence of β2GPI had no effect. Conclusions: β2GPI binds to trophoblast in vitro through its fifth domain, as reported for endothelial cells, and can be recognised by anti-β2GPI antibodies; the antibody binding downregulates trophoblast hCG synthesis and secretion. Such a mechanism might contribute to defective placentation in women with fetal loss associated with the antiphospholipid syndrome.